An attempt at an integrated assessment of the tourism attractiveness of a region: the example of North Karelia (Finland) - Kowalska, Katarzyna (Turyzm/Tourism, 2012)
The article presents a proposal for an integrated assessment of the tourism attractiveness of a region. The holistic approach used in the author's master's thesis is given as an example. The article presents the results of a survey and ‘point bonitation’ (a ranking method) for the North Karelia region. In the summary, there is an attempt to assess the methods which were applied in the research.